POST-PANDEMIC LEARNING POLICY ADAPTATION IN ELEMENTARY SCHOOLS IN YOGYAKARTA - Suyatno, Suyatno; Ndari, Wulan; Sukirman, Sukirman (STKIP Pesisir Selatan, 2026)
COVID-19 pandemic crisis has brought about significant changes in the education process. To address these changes effectively, it is essential to adapt learning policies that suit the specific context of each educational institution. Therefore, this study investigated the implementation of post-pandemic learning policies in elementary schools in Yogyakarta city. Data were collected through interviews, observations, and documentation involving 13 participants, namely two principals, two curriculum coordinator teams, six teachers, and five students. Furthermore, data were analyzed using Milles and Huberman's data analysis approach, aided by Atlas.ti version 8 software. The results showed both similarities and differences in the adaptation of post-pandemic learning policy among the elementary schools in Yogyakarta city. Based on their respective adaptations, these schools exhibited distinct patterns of adaptation. For example, Muhammadiyah Elementary School Warungboto, as a private school, adopted a democratic pattern, guided by public opinion and cooperation, while the public institution leaned towards a hierarchical approach. It was also observed that both public and private schools tailored the learning policy implementation to suit their individual needs and contexts.